The Evaluation of Work Competence of Officers in Tri Rukun Village, Wonosari District, Boalemo Regency - Ni Kadek Adnyani; Darman; Sukrianto (Journal of Economic, Business, and Administration (JEBA), 2020)
ABSTRACT This research aims to find out the competence of the work of the apparatus in Tri Rukun Village, Wonosari district of Boalemo regency. This research method uses descriptive research with a qualitative approach. The data collection techniques used in this study were through observation, in-depth interviews, and documentation of the apparatus in the village government of Tri Rukun village. The results of this study show that the work competence possessed by the apparatus in the village of Tri Rukun has not been optimal. This can be seen from the aspect of knowledge that every apparatus has not been good, including the education and understanding of village officials related to their jobs, further training, and education needs to be done to increase the knowledge of the apparatus. Related to the aspect of the average skill of the village apparatus still has low skills, both in technical skills, skills in community service, and conceptual skills, so it is necessary to hold village apparatus training and placement of officers according to their divisions. In terms of attitude is still not good, it is caused by the lack of sympathy of the apparatus to the orders of the village head, the discipline of the work of the apparatus has not been maximal, the existence of some less social officers, and awareness in the implementation of jobs has not been full. For this reason, the village government needs to be more firm against the regulations that have been set and conduct regular work evaluations.